Reactive Species Interactome Alterations in Oocyte Donation Pregnancies in the Absence and Presence of Pre-Eclampsia - Bos, Manon; Schoots, Mirthe H.; Fernandez, Bernadette O.; Mikus-Lelinska, Monika; Lau, Laurie C.; Eikmans, Michael; van Goor, Harry; Gordijn, Sanne J.; Pasch, Andreas; Feelisch, Martin; van der Hoorn, Marie-Louise P. (International journal of molecular sciences, 2019)
In pregnancy, maternal physiology is subject to considerable adaptations, including alterations in cardiovascular and metabolic function as well as development of immunological tolerance towards the fetus. In an oocyte donation pregnancy, the fetus is fully allogeneic towards the mother, since it carries both oocyte donor antigens and paternal antigens. Therefore, oocyte donation pregnancies result in an immunologically challenging pregnancy, which is reflected by a higher-than-normal risk to develop pre-eclampsia. Based on the allogeneic conditions in oocyte donation pregnancies, we hypothesized that this situation may translate into alterations in concentration of stable readouts of constituents of the reactive species interactome (RSI) compared to normal pregnancies, especially serum free thiols, nitric oxide (NO) and hydrogen sulfide (H2S) related metabolites. Indeed, total free thiol levels and nitrite (NO2−) concentrations were significantly lower whereas protein-bound NO and sulfate (SO42−) concentrations were significantly higher in both oocyte donation and naturally conceived pregnancies complicated by pre-eclampsia. The increased concentrations of nitrite observed in uncomplicated oocyte donation pregnancies suggest that endothelial NO production is compensatorily enhanced to lower vascular tone. More research is warranted on the role of the RSI and bioenergetic status in uncomplicated oocyte donation pregnancies and oocyte donation pregnancies complicated by pre-eclampsia.